The Effect of Storage Conditions and Time on the Antimicrobial Activities of CuO Nanoparticles - Oruc, Cigdem; Celik-Bozdogan, Ays Egul; Kurt-Gur, Gunseli (SPRINGER, 2024)
In recent years, metal and metal oxide, especially copper oxide nanoparticles, have attracted a lot of attention due to their high antimicrobial activity and low-cost advantage, but there are few studies on how storage conditions and time change their effect after the particles are produced. In this study, CuO nanoparticles produced by the sol-gel method and an annealing temperature of 300 degrees C were left in an oxygenated natural environment. Their antimicrobial effects were determined at 3-month intervals for approximately 36 months using Escherichia coli. In addition, the antimicrobial behavior of CuO particles produced at different annealing temperatures (150-900 degrees C) under the same storage conditions was compared. CuO nanoparticle formation was visualized by FESEM and TEM, confirmed by single-phase monoclinic XRD spectra, and characterized by FTIR techniques. It was observed that the antimicrobial effect of CuO nanoparticles prepared at the 300 degrees C annealing temperature and released into the natural oxygen environment decreased by approximately 60% after 36 months. The antimicrobial effect of other CuO particles in oxygen is similar for about 3 years, approximately 10% at 150 degrees C and 20% at 450 degrees C, but no decrease was observed for samples prepared at 600 degrees C annealing temperature. CuO nanoparticles are used in many fields such as health, cosmetic, paint and textile industries due to their antibacterial properties. It is very important to know how long CuO nanoparticles can maintain these antibacterial characteristics. For these reasons, in all these application areas, production with an annealing temperature of 600 degrees C is recommended to maintain the long-term antibacterial effect of CuO nanoparticles.
Keywords: antimicrobial activities; CuO nanoparticles; Escherichia coli; storage conditions; COPPER-OXIDE NANOPARTICLES; PHYSICOCHEMICAL PROPERTIES; SILVER NANOPARTICLES; GREEN SYNTHESIS; Materials Science